Timing of Expansion of Fragile X Premutation Alleles During Intergenerational Transmission in a Mouse Model of the Fragile X-Related Disorders - Zhao, Xiao-Nan; Usdin, Karen (Frontiers in Genetics, 2018)
Fragile X syndrome is caused by the maternal expansion of an unstable CGG-repeat tract located in the first exon of the FMR1 gene. Further changes in repeat number occur during embryogenesis resulting in individuals sometimes being highly mosaic. Here we show in a mouse model that in males expansions are already present in primary spermatocytes with no additional expansions occurring in later stages of gametogenesis. We also show that, in females, expansion occurs in the post-natal oocyte. Additional expansions and a high frequency of large contractions are seen in 2-cell stage embryos. Expansion in oocytes, which are non-dividing, would be consistent with a mechanism involving aberrant DNA repair or recombination rather than a problem with chromosomal replication. Given the difficulty of replicating large CGG-repeat tracts, we speculate that very large expanded alleles may be prone to contract in the mitotically proliferating spermatagonial stem cells in men. However, expanded alleles may not be under such pressure in the non-dividing oocyte. The high degree of both expansions and contractions seen in early embryos may contribute to the high frequency of somatic mosaicism that is observed in humans. Our data thus suggest an explanation for the fact that FXS is exclusively maternally transmitted and lend support to models for repeat expansion that are based on problems arising during DNA repair.